BENTUK, UNSUR, DAN FUNGSI BAHASA RITUAL NYAMBUTIN DI KABUPATEN GIANYAR - Primayanti, Ni Putu Ayus (Humanis, 2013)
‘Nyambutin’ comes from the word ‘sambut’ which could be interpreted as achieve, receive, or seize (PJ Zoetmulder, SO Robson, 2006:1004). When it deeper, ‘sambut’ has a meaning which used to welcome or greeting a baby and Sang Hyang Atma that dwells in the baby’s body. This study is utilize to gather the cultural in a ritual form which mostly find in Bali. The theoretical frameworks which become based of this study were the theory of structuralism and theory of functions. Methods and techniques which applied divided into three stages, at the stage of providing data the researcher used observe method and qualified method; futrhemore, accompanied also with fishing techniques (tekhnik pancing), ‘semuka’ qualified techniques, recording techniques and note technique. Meanwhile in data analysis, the researcher used descriptive method which done along with direct apply element techniques. At last, in presenting results of data analysis, the researcher arranged formal and informal methods, with inductive and deductive thinking techniques. The results of this study show the ritual language of ‘nyambutin’ were in a form of ‘Pujastawa’ and ‘Puja Saa’. The Elements referred to the study were included aspects that form the structure of a language speech: morpheme, word, phrase, clause, and sentence. The functions contained in the ritual ‘nyambutin’ were the Cultural Functions and Personal Functions. Therefore, there are two things state in the Personal function, vision function and information function.
Keywords: forms, elements, functions